Peningkatan Literasi Keuangan dan Pengenalan Investasi Pasar Modal Berbasis Pelatihan Interaktif Pada Siswa Madrasah Aliyah Negeri 1 Pontianak - Lina Budiarti; Arninda Arninda; Amira Violina Erianto (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
Financial literacy levels among high school students remain suboptimal, including at MAN 1 Pontianak. However, understanding financial management and investment is crucial for navigating future economic challenges. In an era of seamless information access and digital investment platforms, appropriate education is the key to ensuring that the younger generation is not only technologically savvy but also financially literate. Through this community service initiative, students were equipped with practical knowledge regarding personal finance and an introduction to capital market instruments, delivered through interactive and applied methods. This program aims to foster a healthy financial mindset from an early age. Evaluation results indicated a significant increase in participants' understanding, with the average pre-test score rising from 49.5 to 87.1 in the post-test. Consequently, this activity proved effective in preparing a more independent, wise, and competitive generation for the modern economic era.